PENGARUH PENDIDIKAN POLITIK TERHADAP TINGKAT PEMAHAMAN PEMILIH PEMULA (Studi Pada Program Pendidikan Pemilu Badan KESBANGPOL Kota Bekasi Tahun 2020) - Achmad Fernanda, (2022)
This study aims to explain how much influence political education has on the level of understanding of novice voters, testing through the election education program of the National Unity and Political Agency of the Bekasi City Government in 2020. The subjects of this study were high school or vocational high school students in Bekasi City, with a population of 300 political education participants who had participated in these activities, using the slovin formula, the sample used was 75 students. The data collection technique used a questionnaire or questionnaire which was used to obtain data on the variable level of political understanding. The analysis requirement test consisted of validity test, reliability test and descriptive analysis. The hypothesis test consists of simple linear regression test, significance test, and coefficient of determination test. The results of the study: there is a relationship that is quite influential between political education on the level of understanding of novice voters. In addition to the answers to the questionnaire, it has also been proven that in the correlation test, the test results are 0.579, which means that there is a significant relationship between the two variables. It can be concluded that, political education on the level of understanding of beginner voters. A significant relationship can be interpreted that the community has a positive perception of political education, so that it can affect the level of understanding of novice voters in the election. Based on calculations using SPSS, obtained from the results of testing the hypothesis of this study amounted to 11.258. The results of this hypothesis test are used to determine the level of significance. In the t table the score is determined at a significant level of 5% and df = n-2 the number of samples, namely 75-2 = 73 and in this case the t table value is 1.666. According to the calculations that have been done, the results obtained are greater than the t table, namely t count 11.258 > 1.666 t table. According to the test results, it can be determined that Ho (there is no influence of political education on the level of understanding of novice voters) is rejected and Ha (there is the effect of political education on the level of understanding of novice voters) is accepted. This means that political education has a very important role for novice voters to prepare themselves to be smart voters in elections. So the more activities or political education programs carried out by the government make the level of understanding of novice voters increase